2015
DOI: 10.5539/ijms.v7n2p35
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Store Atmosphere on Consumer Purchase Intention

Abstract: This paper aimed at identifying the effects of atmosphere on the consumer purchase intention in international retail chain outlets of Karachi, Pakistan. This was the first study, which investigated the collective impact of atmospheric variables at one point in time on purchase intention. This research was causal in nature. A sample of 300 consumers was taken who usually visited these outlets. Data was collected through a well-structured questionnaire and analyzed through regression analysis. Research findings … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
68
2
15

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 103 publications
(91 citation statements)
references
References 24 publications
6
68
2
15
Order By: Relevance
“…In addition that, the results of the statistical analysis showed that the service quality, product quality, brands and logistics are also among the most influential factors which influence to what extent customers are loyal to the store they attend which also rhymed with what Kaura, Prasad, & Sharma (2015) From another perspective, Hussain & Ali (2015) noted in his study the essential and unessential variables that can influence the customer behavior within grocery stores and the different choices of the customers towards choosing the best grocery store. The results of the study showed that price, the physical evidence of the store, the speed of the caching process and the spaces influence the customer loyalty.…”
Section: Relevant Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition that, the results of the statistical analysis showed that the service quality, product quality, brands and logistics are also among the most influential factors which influence to what extent customers are loyal to the store they attend which also rhymed with what Kaura, Prasad, & Sharma (2015) From another perspective, Hussain & Ali (2015) noted in his study the essential and unessential variables that can influence the customer behavior within grocery stores and the different choices of the customers towards choosing the best grocery store. The results of the study showed that price, the physical evidence of the store, the speed of the caching process and the spaces influence the customer loyalty.…”
Section: Relevant Literature Reviewmentioning
confidence: 99%
“…Moreover, store environment, stock quality, and management quality were placed to be precursors of store picture as opposed to segments of store. Many researchers have examined the influence of the store internal environment on the purchasing behavior of the customers, Hussain & Ali (2015) stated that the internal atmosphere of the store influences the customers' purchasing behavior including "cleanliness, scent, lighting, and display/layout" (Hussain & Ali, 2015, p. 35). While Kumar (2010) stated that the atmospheric cues within the store influence the overall evaluation of a customer towards the brands that are being sold and in that sense these cues influence the overall attraction of the customers towards the store in general.…”
Section: Statement Of the Problemmentioning
confidence: 99%
“…Researchers in this research claims that though there is a large number of research in brick and mortar and traditional web retail atmospherics [3], [7], [11], [14], [15], [27], [31], [37], [53], [54], [59], [61], [64], [66], [69], [71], [74]. However, virtual worlds and virtual reality retail stores have existed since 2003 but, research in the context of 3D VRR atmospherics is still at its initial stage [8], [24], [32], [65].…”
Section: B Virtual Reality Retailing (Vrr)mentioning
confidence: 99%
“…Visually, consumers prefer stores with an attractive appearance, neat and clean because it will cause a sense of fun and convenient when visited. The temperature can generate negative emotional feelings if is too high or low (Hussain & Ali, 2015). The smell (aroma), if is very strong, can influencing consumer emotions too .…”
Section: Introductionmentioning
confidence: 99%
“…Convenience store creates store atmosphere to give satisfaction to the consumer (Hussain & Ali, 2015;Massara, 2003;Wilson, 2005). Store atmosphere may be the facilities provided by the store, such as interior and exterior design is attractive, temperature is cool (Lina & Chiang, 2010), the place is clean (Chen & Hsieh, 2011;Nguyen et al, 2015), the layout of the store comfortable (Grewal & Levy, 2007), neat shelves (Keel & Padgett, 2015), adequate lighting (Baker et al, 1992;Verma, 2014), played the right music , the diversity of choice (Kwak et al, 2015), until the store's aroma (Bradford & Desrochers, 2009).…”
Section: Introductionmentioning
confidence: 99%